Analysis of Electrical Power Quality in the 20 kV Distribution Network in the Cikarang Industrial Area - Ariadi, Rizky Pratama; Papadopoulou, Maria Eleni; Nakamura, Kenji (Journal of Engineering and Technological Science, 2026)
Industrial areas demand stable and high quality electrical power to support continuous production processes. The Cikarang Industrial Area is one of the largest industrial zones in Indonesia and relies heavily on a 20 kV medium voltage distribution network. However, increasing nonlinear loads, load imbalance, and network expansion have raised concerns related to power quality issues. This study aims to analyze electrical power quality in the 20 kV distribution network serving the Cikarang Industrial Area. The research applies a quantitative case study approach using field measurements, load flow analysis, and harmonic evaluation based on IEEE standards. Data were collected from selected feeders supplying industrial customers and analyzed using ETAP software. The results show that voltage drop values range from 1.8 percent to 5.2 percent during peak load conditions, while total harmonic distortion of current exceeds recommended limits in several feeders. Load imbalance also contributes significantly to increased power losses. These findings are consistent with previous studies on Indonesian medium voltage networks. The study concludes that power quality in the Cikarang Industrial Area requires systematic monitoring and corrective measures, including load balancing, reactive power compensation, and harmonic mitigation. The results provide practical insights for utilities and industrial consumers to improve network reliability and efficiency.